(untitled) (The Shivapuri Journal, 2024)
There are multiple threats to Nepal’s National Interests. A country with strong political, diplomatic, economic, military, and informational foundations will have multiple policy options, but Nepal does not have that luxury at present. Therefore, Nepal must maintain a strong and professional Nepali Army and other national security institutions to effectively deter and counter possible threats to its National Interests.